How Governments Matter to New Industry Creation - Spencer, Jennifer W.; Murtha, Thomas P.; Lenway, Stefanie Ann (Academy of Management Review, 2005)
We articulate opportunities and challenges for governments and innovating firms operating within countries that display four types of national political institutional structures. We argue that corporatist and associational institutional structures influence governments' capabilities to support diffusion- and mission-oriented technology policies and firms' tendencies to engage in bricolage or breakthrough approaches to technological entrepreneurship. We then show how the relative strength of state institutions can amplify or compromise governments' policies and firms' innovation strategies.